MODELING, DYNAMIC AND THERMAL ANALYSIS OF THE PROTOTYPE MAGNETORHEOLOGICAL CLUTCH - Jerzy BAJKOWSKI (Scientific Journal of Silesian University of Technology. Series Transport)
This paper presents the complex results concerning the prototype clutch with magnetorheological (MR) fluid. The obtained characteristics depicts the dependencies between the clutch’s torque and: the intensity of the magnetic field induced by the coil current, as well as the rotational speed of the rotor, and the temperature of the fluid during exploitation. The research was conducted on the dedicated laboratory stand. The detailed analysis of the results is provided in the article.